Effects of Plant Growth Promoting Rhizobacteria (PGPR) on Growth and Yield of Shallot in Sandy Coastal Land - Sumiyati Tuhuteru; Endang Sulistyaningsih; Arif Wibowo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2016)
The marginal sandy coastal land should be utilized to maintain production level of shallot. But for increasing the productivity of sandy coastal land, in the shallot cultivation should be applied biological fertilizers, such as Plant Growth Promoting Rhizobacteria (PGPR). The purpose of this research was to obtain the most effective isolate of PGPR (Plant Growth Promoting Rhizobacteria) to the growth of three shallot cultivars in the sandy coastal land. The research had been conducted in August-November 2015 at Samas sandy coastal land, Bantul. The Factorial treatments were assigned in Randomized Complete Block Design with three blocks as replications. The first factor was shallot cultivars consisted of Crok, Tiron and Tuk-tuk, while the second factor was the PGPR suspension, i.e. control (without PGPR), PGPR isolates BP25.2 (Bacillus methylotrophicus), BP25.6 (Bacillus amyloliquofaciens), BP25.7 (Bacillus subtilis), BrSM 4 (Burkholderiacepacia), and BrSG 5 (Burkholderiaseminalis). The data of growth and yield were analyzed using ANOVA with α = 5%, then followed by DMRT α 5% . The result showed that Tiron cultivar was able to grow in sandy coastal land, proven from its good germination, high number of bulb, high fresh weight, and dry weight of bulb. Meanwhile, BP25.2 isolate was able to increase seed growth simultaneously of Tiron cultivar and BrSM 4 isolate was able to increase the chlorophyll content of Tuk-tuk cultivars.